From Leaky Gut to Central Nervous System Autoimmunity: Cross-Reactivity and Molecular Mimicry in Schizophrenia - Nowicka, Nina; Mian, Emil; Zapart, Zuzanna; Sikorska, Alicja; Szepietowska, Martyna; Gańska, Oliwia Zuzanna; Bundyra, Jakub; Janik, Dominika; Sochocka, Agata; Parda, Julia (Quality in Sport, 2026)
Background and Aim: Traditional schizophrenia models relying on neurotransmitter dysfunctions are giving way to new perspectives. Stepping beyond the conventional gut-brain axis paradigm, this review emphasizes a fresh autoimmune hypothesis: molecular mimicry and cascading tissue barrier breakdowns as direct triggers of central nervous system (CNS) pathology. Materials and Methods: We analyze recent clinical studies concerning intestinal and blood-brain barrier (BBB) integrity, focusing on specific mechanisms: the kynurenine pathway, cross-reactivity to food antigens (wheat gluten, bovine casein), and NMDA receptor autoantibodies in schizophrenia. Results: Schizophrenia-associated dysbiosis, marked by a depletion of butyrate-producing bacteria, compromises the intestinal barrier, leading to metabolic endotoxemia. Crucially, the pathology is driven by immune deception. Given the structural homologies between foreign or dietary antigens and host tissues (molecular mimicry), cross-reactive lymphocytes and autoantibodies are generated. These penetrate the compromised BBB - sometimes via a macrophage-mediated "Trojan Horse" mechanism - and directly attack host brain structures, including myelin and NMDA receptors. Concurrently, systemic inflammation pathologically redirects tryptophan metabolism, producing neurotoxic kynurenic acid. Conclusions: Schizophrenia's pathophysiology is inextricably linked to immune autoaggression initiated by molecular mimicry. Shifting focus from general microbiome presence to the mechanisms of cross-reactivity and cascading barrier hyperpermeability reveals novel avenues for antigen-specific therapies. Addressing these root causes offers substantial hope for profound clinical improvement or even full remission.